Nanomolar-potency ‘co-potentiator’ therapy for cystic fibrosis caused by a defined subset of minimal function CFTR mutants - Phuan, Puay-Wah; Tan, Joseph-Anthony; Rivera, Amber A.; Zlock, Lorna; Nielson, Dennis W.; Finkbeiner, Walter E.; Haggie, Peter M.; Verkman, Alan S. (Scientific reports, 2019)
Available CFTR modulators provide no therapeutic benefit for cystic fibrosis (CF) caused by many loss-of-function mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel, including N1303K. We previously introduced the concept of ‘co-potentiators’ (combination-potentiators) to rescue CFTR function in some minimal function CFTR mutants. Herein, a screen of ~120,000 drug-like synthetic small molecules identified active co-potentiators of pyrazoloquinoline, piperidine-pyridoindole, tetrahydroquinoline and phenylazepine classes, with EC 50 down to ~300 nM following initial structure-activity studies. Increased CFTR chloride conductance by up to 8-fold was observed when a co-potentiator (termed ‘Class II potentiator’) was used with a classical potentiator (‘Class I potentiator’) such as VX-770 or GLPG1837. To investigate the range of CFTR mutations benefitted by co-potentiators, 14 CF-associated CFTR mutations were studied in transfected cell models. Co-potentiator efficacy was found for CFTR missense, deletion and nonsense mutations in nucleotide binding domain-2 (NBD2), including W1282X, N1303K, c.3700A > G and Q1313X (with corrector for some mutations). In contrast, CFTR mutations G85E, R334W, R347P, V520F, R560T, A561E, M1101K and R1162X showed no co-potentiator activity, even with corrector. Co-potentiator efficacy was confirmed in primary human bronchial epithelial cell cultures generated from a N1303K homozygous CF subject. The Class II potentiators identified here may have clinical benefit for CF caused by mutations in the NBD2 domain of CFTR.